Enhancing Arabic Vocabulary Learning: Development of a Mobile Application Integrating the Quran Arabic Corpus - Rico Fenda Pradana; Kholisin Kholisin; Hanik Mahliatussikah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The Quran Arabic Teaching(QAT) application is an innovative Android-based tool developed to enhance Arabic vocabulary learning, particularly for students at the Jami' Malang Great Mosque Islamic Boarding School. Utilizing the Quran Arabic Corpus (QAC) as its primary resource, the application provides contextual vocabulary learning by exploring word meanings, roots, and usage within Quranic verses. Guided by the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation—the development process ensures the application’s relevance, content quality, and effectiveness in supporting Arabic language education. Results indicate significant positive impacts, with 85% of students reporting increased motivation, 90% showing greater self-will in learning, and 88% benefiting from the flexibility to study independently. Additionally, 92% of students expressed satisfaction with the application’s user-friendly and engaging features. These findings highlight its ability to foster an effective and enjoyable learning environment. Future enhancements, such as speech recognition for pronunciation practice, interactive vocabulary games, and expanded grammar content, are recommended. The application’s integration of Quranic texts enriches linguistic comprehension while deepening appreciation for Islamic scripture. Thus, the QAT application serves as an effective tool in Arabic language learning, offering valuable potential for broader use in Islamic educational settings.